Landscape mosaic for enhancing biodiversity: on what scale and how to maintain it? - Gabay O.; Perevolotsky A.; Shachak M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Successional processes in Mediterranean woodlands are often considered to diminish plant species richness. We investigated the relative importance of both woody and open patches for enhancing plant species diversity and how their effects are scale-dependent and grazing-dependent. Our study site is located in Israel, within a Mediterranean ecosystem characterized by mosaic of shrubs and herbaceous patches. Shrub removal was used to assess the impact of open patches on plant species diversity. The impact was investigated with and without goat grazing and in two spatial scales: cluster of shrubs and 1000 m2 plot. Shrub removal increased plant species richness on a small scale but on a larger scale it resulted in a reduction of species richness. Grazing, however, did not affect species number on both scales. In order to preserve high biodiversity it is advised to remove woody vegetation at small patches while preserving a matrix of intact woody patches. Goats can help in maintaining the desired landscape mosaic without reducing species richness.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)